2022
DOI: 10.1093/eurjpc/zwac056.270
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dilatation using cardiac magnetic resonance in asymptomatic ELITE athletes

Abstract: Funding Acknowledgements Type of funding sources: None. Purpose Aortic dilatation is associated with acute aortic pathology. Cardiac magnetic resonance (CMR) data in asymptomatic elite athletes is lacking. Therefore, we investigated the prevalence of aortic dilatation in a cohort of elite-level athletes using CMR. Methods We performed a cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, recent studies have raised concerns on whether athletes might be at an increased risk of this condition even in the absence of underlying diseases such as Marfan syndrome. A recent report using cardiac magnetic resonance in 164 overall young athletes (mean age, 28 yr) reported that 34% of them showed aortic dilation above normal cutoff values (25). Using cardiac computer tomography, Gentry et al (7) reported a prevalence of 29.5% among former National Football League players (age ~57 yr on average).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have raised concerns on whether athletes might be at an increased risk of this condition even in the absence of underlying diseases such as Marfan syndrome. A recent report using cardiac magnetic resonance in 164 overall young athletes (mean age, 28 yr) reported that 34% of them showed aortic dilation above normal cutoff values (25). Using cardiac computer tomography, Gentry et al (7) reported a prevalence of 29.5% among former National Football League players (age ~57 yr on average).…”
Section: Discussionmentioning
confidence: 99%